Transoral endoscopic radical resection for a recurrent pyriform sinus fistula - Keiichi Morita; Kosaku Maeda; Hiroaki Fukuzawa (Elsevier, 2018)
In revision surgery for a recurrent pyriform sinus fistula (PSF), complete resection of the fistula via a transcervical approach is difficult because of the surrounding scar tissue that results from previous surgery and infections. We successfully performed transoral endoscopic radical resection of the fistula for a recurrent PSF in two patients. Approaching the fistula from the orifice is reasonable and radical resection of the fistula is a reliable procedure in revision surgery. Transoral endoscopic resection is a feasible surgical option for a recurrent PSF. Keywords: Endoscopic surgery, Pyriform sinus fistula, Recurrence, Revision surgery, Transoral surgery